Essays on macroeconomics in Africa - Roger, Lionel Joshua (2018)
This thesis comprises three self-contained essays on topics surrounding economic growth and macroeconomic performance in sub-Saharan Africa (SSA). The first two address aspects of measurement error in macroeconomic data from SSA: the first essay (Chapter 2) explores the potential of nighttime luminosity as a means of improving GDP estimates, the second (Chapter 3) assesses the potential impact of changes in the data on empirical results from time series analysis. The third essay (Chapter 4) investigates exchange rate dynamics in Zambia, and how these pass through to consumer prices.